Role of Sb on the growth and optical properties of 1.55 μm GaInN(Sb)As/GaNAs quantum well structures by molecular beam expitaxy - Sun, Handong (2009)
High-quality GaInN(Sb)As/GaNAs double quantum wells (QWs) which emit at 1.54 mu m wavelength at room temperature with a narrow linewidth of similar to 34 meV (12 meV at 5 K) were fabricated by molecular-beam epitaxy on GaAs substrates. Photoluminescence and photoluminescence excitation spectroscopy were used to study the electronic states and optical properties of these heterostructures. By characterizing samples grown using different fluxes of Sb, the role played by Sb in the growth process and optical properties was elucidated. At low Sb flux, Sb atoms act mainly as a surfactant which improves the microstructure of the QWs and enhances the photoluminescence intensity. With an increase of Sb flux, some of the Sb atoms may incorporate into GaInNAs to form a quinary compound. In the latter case, the incorporation of Sb could also enhance the N composition in the QWs, which may be responsible for the further reduction of the band gap. (C) 2005 American Institute of Physics.